Digital infrastructure development through digital infrastructuring work: An institutional work perspective - YEOW, Adrian (Institutional Knowledge at Singapore Management University, 2025)
Being able to understand and characterize the digital infrastructure development (DID) process has become even more pressing today due to the rapid advent and implementation of new digital infrastructure (DI) in organizations as well as since the COVID-19 crisis. While information systems (IS) research has begun to recognize the institutional nature of such digital infrastructures, there remains a gap in our understanding of how such developments unfold from an institutional perspective. Through our field study of a digital infrastructure development project involving the implementation of an enterprise-wide electronic medical record system at a large US medical facility, we show how the tensions in the DID process were linked to the institutional work these organizational actors performed when they attempted to disrupt and protect the hospital’s institutional arrangement. We introduce the “digital infrastructuring work” concept to describe the combinations of digital object work, DI relational, and DI symbolic work enacted during DID. Specifically, digital object work reveals how material institutional work is directed at multiple DI elements. Our findings also highlight how organizational actors combine DI relational work and DI symbolic work with digital object work to shape the overall DI. As such, our study shows how organizational actors go beyond symbolic and discursive forms of institutional work, and digital object work in particular, to achieve DID outcomes. Future research could explore digital infrastructuring work in different organizational and technological settings.